2001
DOI: 10.1046/j.1365-2141.2001.03002.x
|View full text |Cite
|
Sign up to set email alerts
|

Favourable effect of the combination of acute and chronic graft‐versus‐host disease on the outcome of allogeneic peripheral blood stem cell transplantation for advanced haematological malignancies

Abstract: Summary. To assess the influence of graft-versus-host disease (GVHD) on the outcome of patients with advanced haematological malignancies (AHM) who received a primary, unmodified allogeneic peripheral blood progenitor cells transplant (allo-PBT) from a human leucocyte antigen (HLA) identical sibling donor, we analysed 136 patients with myeloid neoplasms (n 70) or lymphoproliferative disorders (n 66), transplanted at 19 Spanish institutions. Median age was 35 years (range 1±61). The cumulative incidence of rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…Zaucha et al 13 observed that higher doses of CD34+ cells (48.0 Â 10 6 /kg) were associated with a significantly increased risk of extensive cGVHD (HR ¼ 2.3%, 95% confidence interval 1.4-3.7, P ¼ 0.001), rather than a demonstrable impact on survival and relapse. Yet, their results differ from previously published studies 10,20 that report on an inverse association between cGVHD and the risk of relapse, suggesting that the GVL effect carried by allogeneic PBSC grafts is not further improved when clinical symptoms of extensive cGVHD develop. A study 21 conducted by the International Bone Marrow Transplant Registry also inferred that the increased severity of chronic GVHD was not linked to a reduced risk of relapse among HLA-identical siblings receiving conventional stem cell transplantations.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Zaucha et al 13 observed that higher doses of CD34+ cells (48.0 Â 10 6 /kg) were associated with a significantly increased risk of extensive cGVHD (HR ¼ 2.3%, 95% confidence interval 1.4-3.7, P ¼ 0.001), rather than a demonstrable impact on survival and relapse. Yet, their results differ from previously published studies 10,20 that report on an inverse association between cGVHD and the risk of relapse, suggesting that the GVL effect carried by allogeneic PBSC grafts is not further improved when clinical symptoms of extensive cGVHD develop. A study 21 conducted by the International Bone Marrow Transplant Registry also inferred that the increased severity of chronic GVHD was not linked to a reduced risk of relapse among HLA-identical siblings receiving conventional stem cell transplantations.…”
Section: Discussioncontrasting
confidence: 56%
“…In a previous study, 10 cGVHD was associated with a decreased risk of relapse and no significant increase in deaths in complete remission, thereby leading to an increased duration of both disease-free survival and overall survival through the induction of a strong GVL effect in patients with advanced leukemia. Intentional cGVHD or a GVL effect is needed in specific clinical situations where standard allogeneic transplantation by itself does not lead to good survival, such as high-risk ALL (pre-B ALL or Philadelphia chromosome positive ALL), primary refractory leukemia, or CML in blastic crisis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations